10.6k views
2 votes
If you vertically stretch the exponential function f(x)=2^x by a factor of 3, what is the equation of the new function

User SaiBot
by
6.1k points

2 Answers

1 vote

Answer:

f(x)=3(2^x)

Explanation:

(A.P.E.X)

User Kraf
by
5.6k points
2 votes

Answer:


y=3*2^(x)

Explanation:

A vertical stretch of a function means the output values have changed by a factor of 3 or multiplication by 3. Recall, an exponential function has the basic form


y=ab^(2).

If our equation is
f(x)=2^x, then a=1. To stretch it vertically by a factor of 3, we multiply a by 3. So 1(3)=3. The value of a now becomes 3.


y=3*2^(x)

User Edhurtig
by
5.9k points